The impact of the COVID-19 pandemic on perinatal loss among Italian couples: A mixed-method study - Testoni, Ines; Ronconi, Lucia; Iacona, Erika; Trainini, Alice; Tralli, Nella; Nodari, Luisella; Limongelli, Giulia; Cena, Loredana (Frontiers in Psychology, 2022)
Background: Perinatal bereavement is an event that greatly impacts the emotional, psychological, and psychosocial aspects of those who want to have a child. Objectives: Since there are few studies on the psychological impact of the COVID-19 pandemic on couples grieving for perinatal loss, this research aimed to survey this experience. Participants: Between 2020 and 2021, in Italian provinces highly affected by the COVID-19 pandemic, 21 parents participated: 16 mothers (76%; mean age 36.2; SD: 3.1) and 5 fathers (24%; mean age 40.2; SD: 3.4), among which there were 4 couples. Method: A mixed-method design was used through self-report questionnaires and in-depth interviews. Accompanied by a sociodemographic form, the following questionnaires were administered: Prolonged Grief-13, the Parental Assessment of Paternal Affectivity (to fathers), the Parental Assessment of Maternal Affectivity (to mothers), the Dyadic Adjustment Scale short version, the Daily Spiritual Experiences Scale, and the Impact of Event Scale-Revised. The texts obtained through the in-depth interviews underwent thematic analysis. Results: Fifty per cent of participants suffered from Post-Traumatic Stress Disorders (PTSD) symptoms and 20% suffered from relational dyadic stress. Four areas of thematic prevalence emerged: psychological complexity of bereavement, the impact of the COVID-19, disenfranchisement versus support, and spirituality and contact with the lost child. Participants interpreted their distress as related to inadequate access to healthcare services, and perceiving the pandemic restrictions to be responsible for less support and lower quality of care. Furthermore, they needed psychological help, and most of them were unable to access this service. Spirituality/religiosity did not help, while contact with the fetus and burial did. Conclusion: It is important to implement psychological services in obstetrics departments to offer adequate support, even in pandemic situations.